Exercise pulmonary haemodynamics predict outcome in patients with systemic sclerosis. Issue 6 (6th October 2016) - Stamm, Adriana; Saxer, Stéphanie; Lichtblau, Mona; Hasler, Elisabeth D.; Jordan, Suzana; Huber, Lars C.; Bloch, Konrad E.; Distler, Oliver; Ulrich, Silvia
The aim of the present study was to investigate the prognostic value of exercise haemodynamics measured during right heart catheterisation (RHC) in patients with systemic sclerosis (SSc) referred for evaluation of pulmonary hypertension. SSc patients undergoing RHC at rest and during maximal supine incremental cycle exercise were grouped into resting precapillary pulmonary hypertension (PHrest ) (mean pulmonary artery pressure (mPAP) ≥25 mmHg, pulmonary artery wedge pressure <15 mmHg), exercise-induced pulmonary hypertension (PHex ) (mPAP ≥30 mmHg and mPAP/cardiac output >3 mmHg·L −1 ·min −1 at maximal exercise), and without pulmonary hypertension (PHnone ). Patients' characteristics, haemodynamics and follow up data were compared between groups. 72 SSc patients were followed for median (interquartile range) 33 (15–55) months. Mean (95% CI) survival without transplantation estimated by Kaplan-Meyer analysis was 4.4 (0.8–2.9) years in PHrest (n=17), 5.2 (4.4–6.1) years in PHex (n=28) and 9.5(8.4–10.6) years in PHnone (n=27; p<0.05 versus others). In Cox regression models, the exercise-induced increase in mPAP (hazard ratio (HR) 1.097, 95% CI 1.002–1.200) and the coefficient of pulmonary vascular distensibility alpha (HR 0.100, 95% CI 0.012–0.871) controlled for age, but not resting haemodynamics predicted transplant-free survival. Among SSc patients with normal mPAP at rest, an excessive increase in mPAP during exercise and an impaired vascular distensibility may indicate an early stage of pulmonary vasculopathy, associated with reduced survival similar to resting pulmonary hypertension patients. Exercise pulmonary haemodynamics may add important information for management of patients with systemic sclerosis http://ow.ly/Jqkw3034lqp